Anatomy of an epidemic : magic bullets, psychiatric drugs, and the astonishing rise of mental illness in America - Whitaker, Robert (Crown Publishers, 2010)
In this astonishing and startling book, award-winning science and history writer Robert Whitaker investigates a medical mystery: Why has the number of disabled mentally ill in the United States tripled over the past two decades? Every day, 1,100 adults and children are added to the government disability rolls because they have become newly disabled by mental illness, with this epidemic spreading most rapidly among our nation’s children. What is going on?